Potential of Microalgae in Bioremediation of Wastewater - Imran Ahmad; Norhayati Abdullah; I. Koji; A. Yuzir; S.E. Mohamad (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
The increase in global pollution, industrialization and fast economic progress are considered to inflict serious consequences to the quality and availability of water throughout the world. Wastewater is generated from three major sources, i.e. industrial, agricultural, and municipal which contain pollutants, such as: xenobiotics, microplastics, heavy metals and augmented by high amount of carbon, phosphorus, and nitrogen compounds. Wastewater treatment is one of the most pressing issues since it cannot be achieved by any specific technology because of the varying nature and concentrations of pollutants and efficiency of the treatment technologies. The degradation capacity of these conventional treatment technologies is limited, especially regarding heavy metals, nutrients, and xenobiotics, steering the researchers to bioremediation using microalgae (Phycoremediation). Bioremediation can be defined as use of microalgae  for removal or biotransformation of pollutants and CO2 from wastewater with concomitant biomass production. However, the usage of wastewaters for the bulk cultivation of microalgae is advantageous for reducing carbon, nutrients cost, minimizing the consumption of freshwater, nitrogen, phosphorus recovery, and removal of other pollutants from wastewater and producing sufficient biomass for value addition for either biofuels or other value-added compounds. Several types of microalgae like Chlorella and Dunaliella have proved their applicability in the treatment of wastewaters. The bottlenecks concerning the microalgal wastewater bioremediation need to be identified and elucidated to proceed in bioremediation using microalgae. This objective of this paper is to provide an insight about the treatment of different wastewaters using microalgae and microalgal potential in the treatment of wastewaters containing heavy metals and emerging contaminants, with the specialized cultivation systems. This review also summarizes the end use applications of microalgal biomass which makes the bioremediation aspect more environmentally sustainable. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).